(untitled) (Revista Latino-Americana de Enfermagem, 2023)
Objective: to map the expressions of ageism directed to older adults in health services and the respective coping measures. Method: a scoping review of primary studies in English, Spanish and Portuguese, without time delimitation and collected from 14 databases. Selection of the titles, abstracts and full text was in charge of two independent and blinded reviewers, totaling a corpus comprised by 41 articles. Data extraction was performed by pairs. The data were presented in narrative summaries and charts. Results: the ageism expressions are understood at the interpersonal level through images and attitudes that depreciate, devalue life and delegitimize older adults’ needs, as well as at the institutional level, which confers barriers to accessing health services, generating non-assistance and neglect. The coping measures consist of educational interventions and expansion of communication channels between aged people, health professionals and managers. Conclusion: the results may make health professionals vigilant for care/neglect guided by age bias and sensitive for coping with ageism by obtaining diverse scientific knowledge. The analysis of the phenomenon in the Unified Health System context constitutes a knowledge gap, as well as the implicit ageism expressions.